2009
DOI: 10.1123/jis.2.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Transactional or Transformational? Leadership Preferences of Division III Athletic Administrators

Abstract: Leadership research within sport management has yielded inconsistent results when examining transactional and transformational leadership. In addition, there has been a paucity of research comparing leadership behaviors between men and women based on leadership style. Therefore, this study examined whether leadership style (transactional, transformational) led to more positive perceptions of organizational outcomes in intercollegiate athletic administration and whether gender of the leader influenced these per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 19 publications
5
59
2
1
Order By: Relevance
“…Unlike Burton and Peachey (2009), there was a strong positive relationship between transformational leadership and leader effectiveness. This relationship was strongest with the charisma and individualized consideration dimensions of transformational leadership.…”
Section: Transformational and Transactional Leadership Stylescontrasting
confidence: 54%
See 2 more Smart Citations
“…Unlike Burton and Peachey (2009), there was a strong positive relationship between transformational leadership and leader effectiveness. This relationship was strongest with the charisma and individualized consideration dimensions of transformational leadership.…”
Section: Transformational and Transactional Leadership Stylescontrasting
confidence: 54%
“…In a recent study with Division III athletic directors in the U.S., for instance, Burton and Peachey (2009) found that transformational leadership was positively associated with perceived extra effort and satisfaction with the leader, but not with leader effectiveness. Transformational leadership was also the preferred leadership behavior overall, regardless of whether this style was displayed by a male or female leader.…”
Section: Transformational and Transactional Leadership Stylesmentioning
confidence: 96%
See 1 more Smart Citation
“…In support of this immense impact, the Gross Domestic Sports Product (GDSP) in the U.S. was reported at $189.338 billion in 2011 (Milano and Chelladurai, 2011). Although leadership is perceived as having a significant influence on organizational success in the sport industry, gender diversity within its hierarchy is scarce (Burton and Peachey, 2009). As such, the sport industry represents a rich investigative domain for the examination of factors impacting the leadership development of women.…”
Section: Previous Researchmentioning
confidence: 99%
“…Burton and Welty Peachey (2013) suggested investigating if intercollegiate athletic administrators adopting servant leadership behaviors might influence different responses to ethical issues facing the commercialization within intercollegiate athletics. While two studies were found that specifically examined leadership in Division III, including one on the effects of transactional and transformation leadership (Burton & Welty Peachey, 2009) and the other on the impact of leadership style and organizational goals on emotional exhaustion, job stress, and personal accomplishment (Ryska, 2002), NCAA Division I athletics programs get most of the media exposure and are most often studied by sport management scholars (e.g., Burton, Welty Peachey, & Wells, 2017;Gaul, 2015;Gurney, Lopiano, & Zimbalist, 2017). To address the void of information about NCAA Division III institutions, this study examined the relationship between servant leadership and ethical climate in NCAA Division III athletic departments.…”
mentioning
confidence: 99%